(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the influence of the family environment on the reading interest of eighth-grade students at SMP Negeri 2 Kubung. The study used a quantitative approach with an associative research type. The study population was all 88 eighth-grade students of SMP Negeri 2 Kubung, with a sampling technique using total sampling. Data were collected through questionnaires and analyzed using simple regression analysis. The results showed that the family environment had a positive and significant effect on students’ reading interest, indicated by a significance value of 0.000 (<0.05). The research findings revealed that a supportive family environment, such as providing motivation, exemplary reading, and the provision of reading materials, contributed to increasing students’ reading interest. The contribution of the family environment to reading interest reached 32.3%, while the remaining 67.7% was influenced by other factors, such as peers, school facilities, technological developments, and students’ intrinsic motivation. The results of the study confirmed that the family has an important role in shaping students’ reading habits and interests.